Mathematical Modeling on Cardiography: Advancements in Mathematical Modeling for Cardiography (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Modern medical sciences have led to new prospects of improved medical health care in which mathematical modeling becomes increasingly important and will predict behavior of the human body as a response to internal or external changes. Due to the physical complexity and difficult experimental accessibility of biological systems, mathematical modeling has not enjoyed a comparable interest. Consequently, medical treatment at present is still mainly based on consensus about the behavior of the human body and rarely supported by predictive modeling. The present paper provides some aspects of mathematical modeling in cardiography.